Analisis Hukum Islam terhadap Sanksi Pembatalan Khithbah Nikah - Sudirman Sudirman (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2017)
Khithbah is an important process in marriage because it becomes the gateway. In order to maintain the continuity of the process towards the marriage level and keep the parties from the losses due to the unilateral cancellation of khithbah that is rampant, the leaders of Gaya Baru 3 and Gaya Baru 5 make a khitbah agreement with certain sanctions. This paper examines how the covenants of khitbah, peningset, and other material fines and their implications for the maqashid of sharia. The finding is that the practice of the khitbah covenant can be justified in the spirit of the Compilation of Islamic Law and the opinion of the madhhab scholars. It's just that the nominal fines are too large to make the parties objected so do legal hillah that actually hit the maqashid sharia of marriage.